2021
DOI: 10.1186/s40635-021-00424-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cell-based therapies for severe viral pneumonia: therapeutic potential and challenges

Abstract: Severe viral pneumonia is a significant cause of morbidity and mortality globally, whether due to outbreaks of endemic viruses, periodic viral epidemics, or the rarer but devastating global viral pandemics. While limited anti-viral therapies exist, there is a paucity of direct therapies to directly attenuate viral pneumonia-induced lung injury, and management therefore remains largely supportive. Mesenchymal stromal/stem cells (MSCs) are receiving considerable attention as a cytotherapeutic for viral pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…In addition to the above described effects, antiviral properties have also been attributed to MSCs and MSC-EVs. MSCs could inhibit virus replication and shedding through IDO and LL37 secretion and improve influenza-induced viral pneumonia and ARDS due to anti-inflammatory and reparative potential, partly through the interaction with Mφ [ 182 , 183 ].…”
Section: Therapeutic Potential Of Msc-mφ Interaction and Lung Injury ...mentioning
confidence: 99%
“…In addition to the above described effects, antiviral properties have also been attributed to MSCs and MSC-EVs. MSCs could inhibit virus replication and shedding through IDO and LL37 secretion and improve influenza-induced viral pneumonia and ARDS due to anti-inflammatory and reparative potential, partly through the interaction with Mφ [ 182 , 183 ].…”
Section: Therapeutic Potential Of Msc-mφ Interaction and Lung Injury ...mentioning
confidence: 99%
“…RGD-hydrogel improved MSC survival but not cell engraftment in the lung. This result varied with the orthotopic transplantation of exogenous MSCs into dense tissues, such as ischemic myocardium [ 33 ] and injured brain [ 34 ], which could be attributed to the insufficient adhesion between the cells and lung lacunar parenchyma [ 35 ]. Hence, RGD-hydrogel has the potential to enhance lung injury repair by increasing MSC secretion and survival.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that clinical and pilot uncontrolled trials based on MSCs experienced an explosive increase due to the global pandemic of COVID-19 (Khoury et al, 2020). The systematic reviews and meta-analyses examining clinical studies based on the use of MSCs for COVID-19 ARDS agree that MSCs were safe, showed no detection of serious adverse events and were associated with a reduction in mortality and time to recovery compared to controls (Masterson et al, 2021;Chen et al, 2022;Kirkham et al, 2022).…”
Section: Introductionmentioning
confidence: 99%